Entrepreneurial Competencies and Readiness of Extension Service Beneficiaries of a State University - Desiree Joy D. Perez; Joseph G. Guevarra (Philippine Social Science Journal, 2020)
Entrepreneurship as a pillar of a country’s economy improves the quality of life of the people.  Using the descriptive research design, the study aimed to assess the entrepreneurial competencies and readiness of extension and community service beneficiaries of training on transferred technology of a state university in Negros Occidental, Philippines.  A researcher-made questionnaire was utilized to gather data from randomly selected respondents.  Using mean, results showed moderate entrepreneurial competencies and high entrepreneurial readiness.  Likewise, the results of Kruskal Wallis revealed that significant differences occurred both in competency and readiness when respondents are grouped by educational attainment and entrepreneurial training.  Moreover, employing Spearman rho, a significant relationship was found between entrepreneurial competencies and readiness.  Findings aver that the economic advancement of the individual is a result of investment in human capital.  In view of community empowerment, the entrepreneurship development plan formulated will supplement the existing program of the institution.